2017
DOI: 10.3389/fimmu.2017.00299
|View full text |Cite
|
Sign up to set email alerts
|

Disease Phenotype and Outcome Depending on the Age at Disease Onset in Patients Carrying the R92Q Low-Penetrance Variant in TNFRSF1A Gene

Abstract: BackgroundTumor necrosis factor receptor-associated periodic syndrome (TRAPS) is an autosomal-dominant autoinflammatory disease caused by mutations in the TNFRSF1A gene. R92Q, a low-penetrance variant, is usually associated with a milder TRAPS phenotype than structural or pathogenic mutations. No studies differentiating R92Q-related disease in patients with pediatric and adult onset have been performed to date.ObjectiveTo analyze clinical features and disease outcomes in patients diagnosed with TRAPS associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 28 publications
1
26
1
5
Order By: Relevance
“…This treatto-target approach successfully controls disease activity and can prevent organ damage in patients with AIDs [59]. In contrast, there is a very mild AID phenotype with limited disease activity: some CAPS patients experience significantly fewer symptoms during warm seasons, TRAPS patients may have very infrequent episodes of clinically active disease [60]. In addition, the risk of organ damage may differ dramatically between AID patients as demonstrated for the risk of hearing loss in CAPS [40].…”
Section: Discussionmentioning
confidence: 99%
“…This treatto-target approach successfully controls disease activity and can prevent organ damage in patients with AIDs [59]. In contrast, there is a very mild AID phenotype with limited disease activity: some CAPS patients experience significantly fewer symptoms during warm seasons, TRAPS patients may have very infrequent episodes of clinically active disease [60]. In addition, the risk of organ damage may differ dramatically between AID patients as demonstrated for the risk of hearing loss in CAPS [40].…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, the R92Q mutation is currently classified as a variant of uncertain significance, and its pathogenic role in causing TRAPS phenotypes is already controversial [29]. When considered pathogenic, it has been associated to a protean clinical phenotype consisting in fever, abdominal pain, arthralgia/arthritis, fatigue, myalgia, and less frequently headache, odynophagia, skin rash, and chest pain with a broad range of age at disease onset [3]. In line with previous evidences, in our cohort of patients carrying R92Q variant, disease onset was quite varied (ranging 1 to 54 years), with frequent flares lasting 12 days on average characterized by musculoskeletal symptoms, lymphadenopathy, skin rash, and chest pain as most frequently complained symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…According to criteria used in previous studies, patients aged <16 and ≥16 years at disease onset were considered to have pediatric and adult disease onset, respectively [2,3,14,15]. In order to distinguish patients according to genotype, we divided the cohort into two main groups: patients carrying TNFRSF1A HP mutations (HP group) and patients carrying TNFRSF1A LP mutations (LP group).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the low-penetrance variants appear to produce their effects through a different pathophysiological mechanism compared with clearly pathogenic gene alterations, and are, at least in part, connected to the functional status of regulatory T cells [19]. An analysis of a series of patients who carry a well characterized low-penetrance variant has shown that severity of symptoms and risk of complications are highly variable and at least partially correlated with the age of onset [20]. In the light of all this, it appears quite justified to speak of a "TRAPS spectrum" as a diagnostic category (as opposed to the diagnosis of TRAPS per se).…”
Section: Discussionmentioning
confidence: 99%